ضمانات حقوق الانسان وارتباطها بالتنمية الاقتصادية - البياتي اياد خضر عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Economic rights are among the important rights that most countries work to document in the constitutional document to ensure that they are preserved from infringement by public authorities. At the international level, countries have shown interest in these rights, as the United Nations adopted an international covenant on economic rights in 1966. In order to develop the economy of countries and raise the standard of living of individuals, governments must work to master the management of their natural resources, provide job opportunities for their individuals, and eliminate the level of unemployment. We find that the Iraqi constitution stipulates economic rights while providing political and legal guarantees for these rights, but merely stipulating these rights does not It is enough, but it needs real work to develop it, and this is what we found in Iraq. Despite the availability of multiple natural resources, their mismanagement was the reason for the decline of the Iraqi economy and the widespread phenomenon of unemployment.